Clinico-pathological Study of Solid Cancer patients receiving chemotherapy at Birat Medical College Teaching Hospital - Sapkota, Sulav; Priyadarshini, Mona (Birat Journal of Health Sciences, 2022)
Introduction: Solid cancers are increasing in eastern region of Nepal. There are very few centers providing chemotherapy treatment to solid cancer patients in eastern region of Nepal. Objectives: The aim of this study is to stratify the types of solid cancers and study their socio-demographic and clinicopathological features of solid cancer. Methodology: This descriptive cross sectional study was conducted from 1st September 2020 to 1st july 2021 at the department of Oncology . All the histologically proven patients of solid cancers, derived from solid organs like lung, stomach, liver, breast etc, receiving chemotherapy during the study period were taken as study population. All the relevant data were entered in the excel sheet and analyzed by the help of statistical software. Result: There were total seventy three cases who got admitted for chemotherapy during the study duration at the department of Oncology. The patients were between 30-85 years, with the mean age of 59 years and the proportion of females were almost double (64%) than male. 78% cancers were advanced staged in contrast to 22% early stage cancers. Cases were majorly with clinical remission (30%) out of which most common were breast and colorectal cancers. Total 58% of the cases were alive while 42% of the cases expired during the study period. Conclusion: There is a need of comprehensive cancer center in eastern region of Nepal due to increase in the burden of solid cancers.